The Effect of Extraction Condition on The Polyphenol Content and Antioxidant Activity of Curcuma zedoaria (Christm.) Roscoe Rhizome - Marliani, Lia; Budiana, Wempi; Anandari, Yonara (Indonesian Journal of Pharmaceutical Science and Technology, 2017)
White turmeric (Curcuma zedoaria (Christm.) Roscoe) is one of Indonesian herbal medicine. The extraction process to get active compound was influenced by some factor such as solvent, temperature, time, and method of extraction. The objective of this study was to determine the significant factor of extraction  that is solvent, temperature and time of extraction on the polyphenol content and antioxidant activity of white turmeric (Curcuma zedoaria (Christm.) Roscoe) rhizome. Extraction was done by dynamic maceration method with variations (23 factor variable design) of solvent (ethanol 95% and water), temperature (25°C and 70°C), time (6 and 24 hours). The method of analysis of polyphenol content using Folin Ciocalteu reagent, and the antioxidant activity using DPPH free radical reduction method. The experiment design and data analysis using software Design Expert ver.10. The result showed that extraction using ethanol 95% at 70°C for 24 hours was gave high polyphenol content and antioxidant activity. Data analysis was showed that polyphenol content and antioxidant activity was influenced only by solvent of extraction. This study indicated that solvent is significant extraction factor for polyphenol content and antioxidant activity of white turmeric (Curcuma zedoaria (Christm.) Roscoe) rhizome. Keywords: Antioxidant, Curcuma zedoaria (Christm.) Roscoe, extraction, polyphenol